If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(-5b + 4) = 14 + 8b Reorder the terms: -5(4 + -5b) = 14 + 8b (4 * -5 + -5b * -5) = 14 + 8b (-20 + 25b) = 14 + 8b Solving -20 + 25b = 14 + 8b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-8b' to each side of the equation. -20 + 25b + -8b = 14 + 8b + -8b Combine like terms: 25b + -8b = 17b -20 + 17b = 14 + 8b + -8b Combine like terms: 8b + -8b = 0 -20 + 17b = 14 + 0 -20 + 17b = 14 Add '20' to each side of the equation. -20 + 20 + 17b = 14 + 20 Combine like terms: -20 + 20 = 0 0 + 17b = 14 + 20 17b = 14 + 20 Combine like terms: 14 + 20 = 34 17b = 34 Divide each side by '17'. b = 2 Simplifying b = 2
| 8+11=20 | | 3(3y-11)=-6(y+4) | | (4x)(7y)-(x)(3y)= | | 40=-10x | | 3x-2x+7x=-24 | | 12-17=139 | | 3y+9=5y-3y | | -2n+6n=16 | | -1.4=2x | | 25x^2+10x+-8= | | 8D=5F | | -8(3b+4)+(25b-5)=0 | | -6f+13=2f | | 5+4(3x-8)-2(x+6)=x-9 | | 8n+22=-2(-4n+3)+7n | | r+8.4=-0.5 | | 6=-3(r+2) | | w^2+2w=99 | | 4a=a-18 | | 2=2x-6 | | -3n+30=-6(6+6n) | | 3x^3+25=x^2+75 | | 13=3n+6-8 | | 8b-12b+10b= | | x^2+3x-72=4x | | 9l=3l+3m | | 0.66X-16=0 | | 6(w-1)=3(w+5) | | 26-5x=-7(x-4) | | (-8y-5)(7y)*y=-3 | | 5p+2=11+4p | | 57=-7(7b-3)-(7-6b) |